Reportage Stories about Ethnic Conflicts in the World of Uprooted People - Wiszniowska, Monika (Sensus Historiae, 2020)
It was at the turn of the century when Ryszard Kapuściński, observing the problems of surrounding world, seeing the changes of this world, noticing the danger such as racism, nationalism and religious fanaticism presented an extremely important statement. He was convinced that these “twenty first century plagues” were the result of loss of our stable individual and collective identity. He pointed that this loss, due to the fact that people lose they roots, was the major reason of fear and animosity among the people, especially to Strangers. Kapuściński was of the opinion that people who had problems with their own identity did not want to give the equal status to Strangers, which led them to fundamentalism. This statement is also accepted by literature journalists of the younger generation. One can find the illustration of this problem in the books Planeta Kaukaz (Planet Caucasus) by Wojciech Górecki or Wszystkie wojnyLary (All Lara’s Wars) by Wojciech Jagielski. These authors, seeing the ethnic conflicts in Caucasus, Balkan or Northern Ireland show in very interesting form how the “liquid”, non-stable identity of the local people became probably the most important cause of this fanaticism development.